The Role of Sustainability Accounting in Supporting Sustainable Development Goals (SDGs): A Case Study of Manufacturing Companies in Indonesia - WIRANTI, Tia; PUTRI, Trisna Arya; JUNIARI, Diah; PRATIWI, Nindya Ayu (PT Batara Swastika Harati, 2025)
Sustainability accounting has become an important element in supporting the achievement of Sustainable Development Goals (SDGs) in various sectors, including the manufacturing industry in Indonesia. This study aims to analyze how sustainable accounting practices, including environmental accounting and sustainability control systems, can contribute to the achievement of SDGs, especially in the context of manufacturing companies. This study uses a literature study approach that integrates various related literatures to explore the relationship between sustainable accounting and goals such as poverty alleviation, environmental protection, and improving community welfare. The results of the study indicate that the implementation of sustainable accounting, such as sustainability reporting and ERP-based accounting information systems, can improve transparency, accountability, and operational efficiency of companies, while supporting the achievement of SDGs. However, challenges such as lack of consistent regulations, high implementation costs, and limited human resources are still obstacles. This study suggests that manufacturing companies in Indonesia strengthen the integration of sustainable accounting with their business strategies to achieve a more significant impact on SDGs.